FAKTOR YANG MEMPENGARUHI VOLATILITAS HARGA SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Cahyadi, Jeremy; Nariman, Augustpaosa (Jurnal Paradigma Akuntansi, 2025)
This research aims to find out how the factors in this study influence stock price volatility consisting of stock trading volume, dividend policy, and asset growth with firm size as a moderating variable in manufacturing companies in consumer non cyclical and healthcare sectors listed on Indonesia Stock Exchange in 2019-2021. Sampling in this study used purporsive sampling method which resulted a total sample of 93 data from 31 companies. Data processing technique in this study used multiple regression analysis which was processed using E-views 12.0 program. The results of this study indicate that stock trading volume has a significant positive effect on stock price volatility, dividend policy has non significant negative effect on stock price volatility, asset growth has non significant positive effect on stock price volatility. In addition, firm size does not moderate the effect of stock trading volume on stock price volatility, firm size does not moderate dividend policy on stock price volatility, and firm size does not moderate asset growth on stock price volatility.